PENERAPAN TEKNIK TIGA FASE (THREE PHASE TECHNIQUE) UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA DALAM MENULIS ESAI DESKRIPTIF - Esti Kurniasih, (Pelangi Ilmu, 2010)
Abstract Three Phase Technique is a technique which consists of prewriting stage, writing stage, and revising. In this technique, the students are required to prepare themselves from pre writing stage to revising stage. This article describes (1) How Three Phase Technique was implemented to improve the third semester college students of English Education in developing the introductory paragraph (Identification) of descriptive essay and (2) How  Three Phase Technique was implemented to improve the third semester college students of English Education in developing the body paragraph (Description) of descriptive essay? The result of the research in general showed that (1) Three Phase Technique can improve the students ability in writing descriptive essays; (2) Every stage in this technique is very helpful for the students to write descriptive essay, (3) The first stage of this technique (i.e. determining topic and making strategic questions) helps the students to develop the introductory paragraph (Identification) of descriptive essay; (4) All activities in prewriting stage help the students to develop the body paragraph (Description) of descriptive essay. Those activities are determining topic, finding the keywords related to the topic (brainstorming), making strategic questions, and making mind mapping; and (5) The last stage of this technique, i.e. revising, also helps the students to improve their ability in writing descriptive essays.